Lithium-based sorbents for high temperature CO2 capture: Effect of precursor materials and synthesis method. (15th October 2018) - Izquierdo, M.T.; Gasquet, V.; Sansom, E.; Ojeda, M.; Garcia, S.; Maroto-Valer, M.M.
Highlights: Fly ash and pure reagents are used to obtain Li-based sorbents. Solid state and precipitation methods are used to obtain Li-based sorbents. CO2 uptake is near theoretical one only with sorbent synthetized from pure reagents. The fly ash dilution effect alone cannot explain poor CO2 uptake performance. Balance between compounds content/CO2 theoretical capacity predicts sorbent uptake. Abstract: The aim of this work was to study the effect of the silica source (pure reagent or fly ash, FA) and preparation method (solid state reaction and precipitation method) using Li-pure reagents on the CO2 uptake at high temperature of the prepared sorbents. CO2 uptake of sorbents prepared from pure reagents or FA was compared. A relationship between surface area, pore volume and particle size with CO2 uptake of the prepared samples was not found. X-ray diffraction (XRD) characterization revealed different Li4 SiO4 contents in the produced samples. Sample prepared from Li2 CO3 and SiO2 pure reagents by solid state method had a high Li4 SiO4 content (91.5 wt%), but in the presence of FA the main compound was Li2 CaSiO4, which has a low theoretical CO2 uptake capacity. There is a negligible effect of the preparation method on samples prepared from LiOH with either pure silica or FA. However, for pure reagents (LiOH and SiO2 ), the Li4 SiO4 content was lower than that found when Li2 CO3 was used as starting material, probably due to a lower synthesis temperature. For LiOH-FA derived samples, XRD patterns showed that CaO was the main crystal phase and the Li content was low, indicating that this element was probably present in the amorphous phase. Except for the Li4 SiO4 rich sample, a linear relationship was found between the experimentally measured CO2 uptake and the theoretically calculated one based on the stoichiometry of carbonation reactions exhibited by active phases contained within each sorbent, and normalised to crystal phase contents. Despite the high CaO content in some of the FA-derived samples, the carbonation reaction does not proceed via CaCO3 formation and Li2 CaSiO4 and Ca5 (SiO4 )2 CO3 crystal phases are present in the carbonated samples, limiting the CO2 capture of CaO present in the fly ash.